2018
DOI: 10.2337/dc17-1309
|View full text |Cite
|
Sign up to set email alerts
|

BMI and Mortality in Patients With New-Onset Type 2 Diabetes: A Comparison With Age- and Sex-Matched Control Subjects From the General Population

Abstract: Our findings suggest that the apparent paradoxical findings in other studies in this area may have been affected by reverse causality. Long-term, overweight (BMI 25 to <30 kg/m) patients with type 2 diabetes had low excess mortality risk compared with control subjects, whereas risk in those with BMI ≥40 kg/m was substantially increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 30 publications
3
23
0
1
Order By: Relevance
“…Although the majority of research supports the existence of the obesity paradox, a growing body of literature suggests that this observation might be biased by reverse causality or unknown confounders. [9][10][11] Differences in the sample populations may be responsible for the inconsistent results. 12 Specifically, Lee et al 13 reported that the optimal body mass index (BMI) for survival depends on the patient's glucose regulation status.…”
Section: Introductionmentioning
confidence: 99%
“…Although the majority of research supports the existence of the obesity paradox, a growing body of literature suggests that this observation might be biased by reverse causality or unknown confounders. [9][10][11] Differences in the sample populations may be responsible for the inconsistent results. 12 Specifically, Lee et al 13 reported that the optimal body mass index (BMI) for survival depends on the patient's glucose regulation status.…”
Section: Introductionmentioning
confidence: 99%
“…This was done in part to prevent small cohort numbers, but the sensitivity of the effect of insulin treatment during pregnancy may have been lost, resulting in non-signi cant results. Studies show that the effects of BMI on health and mortality is heterogenous and becomes increasingly worse with increasing BMI class [40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…The top three risk factors for women in 2016 were high blood pressure, high body-mass index (BMI) and high fasting plasma glucose [14]. The increasing BMI of the population is of major concern in Sweden [15] as well as in most other countries (including both high and low-income countries). Recent reports [16,17] from Sweden estimated the prevalence of overweight (BMI 25-29.9 kg/m 2 ) to be about 30% for women and about 45% among men.…”
Section: Introductionmentioning
confidence: 99%